A Novel Sensor from Cyclotriveratrylene Derivative for Rapid Detection of 4-Nitrophenol Based on Fluorescence - F. Fern, Patrick; R. Mishra, Divya (Asian Journal of Chemistry, 2020)
In order to study various environmental pollutants among the class of nitro aromatic compounds, a new and novel sensor derived from a cyclotriveratrylene derivative has been developed which rapidly detects 4-nitrophenol from among the class of nitro aromatic compounds via spectrofluorimetric method. The newly derrivaritized cyclotriveratrylene compound is successfully confirmed by using the available techniques of 1H NMR, 13C NMR and ESI-MS. The newly developed molecule was named 4C7NbF-CTV. The complexation behaviour of 4C7NbF-CTV with various nitro aromatic compounds was studied. In the absorption spectra a shift was observed, which indicated that 4-nitrophenol interact with 4C7NbF-CTV. An enhanced intensity of fluorescence of 4C7NbF-CTV was observed on adding 4-nitrophenol.